Carbapenemase-producing Klebsiella quasipneumoniae ST688 (NDM-1) and Klebsiella michiganensis ST40 (KPC-2) in food destined for hospitalized patients - Godoy, Bianca L.V.; Barroso, Marlon do Valle; Dantas, Karine; Rodrigues, Vitória G.T.; Ferreira, Taís P. [UNESP]; Atuí, Caroline; Valle, Ana C.; Fuga, Bruna; Lincopan, Nilton; Nogueira, Mara C.L.; Casella, Tiago (Elsevier, 2024)
Objectives: Klebsiella spp. are leading causes of nosocomial infections. Their ability to harbour antimicrobial resistance genes makes them an important public health threat. This study aimed to report the genomic background of carbapenemase-producing Klebsiella quasipneumoniae (HV55B) and Klebsiella michiganensis (HV55D) strains isolated from fresh vegetables destined for hospitalized inpatients. Methods: Microbiological and molecular methods were used to isolate and identify the strains, which were submitted to the antimicrobial susceptibility test and pH tolerance assays. Whole genome sequencing was performed on MiSeq and NextSeq platforms, and online available tools were applied to bioinformatic analysis of clinically relevant information. Results: Both isolates were considered multidrug-resistant and tolerated pH ≥ 4 for 24 h. HV55B belonged to sequence type (ST) ST668, and presented a broad resistome and plasmids from four incompatibility groups. HV55D belonged to ST40. Both strains HV55B and HV55D were genetically close to isolates responsible for human infections around the world, which stands for the plausibility of such bacteria to cause disease in patients of the studied institution. Conclusions: Our results confirm the presence of carbapenemase-producing Klebsiella spp. in fresh foodstuffs intended for hospitalized inpatients’ consumption. The genomes characterized here also provide clinically and genomically relevant information to forthcoming epidemiological surveillance studies.
Keywords: Genomic surveillance; Klebsiella michiganensis; Klebsiella quasipneumoniae; KPC-2; NDM-1